2015
DOI: 10.1177/1054773815586542
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Behaviors and Glycemic Control in Low-Income Adults in México With Type 2 Diabetes Mellitus May Have Implications for Patients of Mexican Heritage Living in the United States

Abstract: This study examined self-care behaviors and their relationship to glycemic control in low-income Mexican adults with type 2 diabetes in Southeastern Tamaulipas, México. A total of 135 patients were enrolled from 17 community health centers. The most frequent self-care behavior was medication management (80%), and the least frequent self-care behavior was self blood glucose monitoring (7%). All the patients demonstrated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…This finding has also been reported in low-income adults with T2DM. 39 Participants were low income, had limited education, and had low dietary intake of fruits and vegetables as in our study. Dietary changes have consistently been reported to be the most difficult, especially in low-income persons with diabetes, as factors such as culture, lifelong habits, and family and socioeconomic resources influence dietary intake.…”
Section: Discussionmentioning
confidence: 93%
“…This finding has also been reported in low-income adults with T2DM. 39 Participants were low income, had limited education, and had low dietary intake of fruits and vegetables as in our study. Dietary changes have consistently been reported to be the most difficult, especially in low-income persons with diabetes, as factors such as culture, lifelong habits, and family and socioeconomic resources influence dietary intake.…”
Section: Discussionmentioning
confidence: 93%
“…15 Several studies showed that training on self-care behaviors, drug use, self-monitoring of blood sugar, diet, exercise, and foot care, sufficient knowledge about self-care in diabetes was associated with lower HbA1c level. [16][17][18][19] The requirement of adherence to diabetes self-care behavior such as adherence to medication, exercise, diet, and self-monitoring of blood glucose familiarize diabetes patients to avoid, and free from fears that they have diabetes. This robust routine diabetes self-management leads to good glycaemic control and subsequently reduces the risk of diabetic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that training on self-care behaviors, drug use, self-monitoring of blood sugar, diet, exercise, and foot care, sufficient knowledge about self-care in diabetes was associated with lower HbA1c level. 16 19 …”
Section: Introductionmentioning
confidence: 99%
“…Different interventions have been developed to control diabetes in primary care without satisfactory results, showing the need for new strategies for management of this disease. Home visits are considered an economical and effective method for preventing and controlling chronic diseases, as they can provide benefits for the patient, their family and society in general, as well as improve the quality of life among old patients with chronic disease.…”
Section: Introductionmentioning
confidence: 99%